2018
DOI: 10.1111/jphp.12985
|View full text |Cite
|
Sign up to set email alerts
|

Differences in drug quality between South Africa and Germany

Abstract: Important differences in quality were detected between some German and South African products. To preclude drug products of poor or doubtful quality from entering the market in South Africa, countermeasures are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(64 reference statements)
0
2
0
Order By: Relevance
“… 15 Here, samples of difficult-to-make drug products were procured and tested directly by the FDA. Drug sampling studies are needed because such studies in other countries, especially developing countries, have shown serious issues with drug quality, 16 , 17 , 18 , 19 often associated with counterfeiting. 20 Beyond this study, the FDA regularly samples drugs for surveillance and other reasons and takes action when occasionally finding substandard products from all regions.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Here, samples of difficult-to-make drug products were procured and tested directly by the FDA. Drug sampling studies are needed because such studies in other countries, especially developing countries, have shown serious issues with drug quality, 16 , 17 , 18 , 19 often associated with counterfeiting. 20 Beyond this study, the FDA regularly samples drugs for surveillance and other reasons and takes action when occasionally finding substandard products from all regions.…”
Section: Discussionmentioning
confidence: 99%
“….]" 15 or with the capacity of local regulators to detect insufficient standards. Harming is not the primary intent of such practices, but the primary intent (cutting costs) implies accepting the risk of harming.…”
Section: From Who Definitions To National Legislationsmentioning
confidence: 99%